PENETAPAN TEMPAT KHUSUS PARKIR DI KAWASAN OBJEK WISATA KULINER CIMANUK INDRAMAYU BERDASARKAN PERATURAN DAERAH NOMOR 16 TAHUN 2017 PENYELENGGARAAN PERPARKIRAN DI KABUPATEN INDRAMAYU - Siregar, Syamsul Bahri; Susanti Dwi Sonjaya, Suchi (Yustitia, 2021)
The increasing use of private transportation, now more and more public places that provide vehicle storage facilities in their area. This vehicle storage is better known as parking by the community. In Article 1 No. 14 of the Regional Regulation of Indramayu Regency Number 16 of 2017 concerning Parking Management which states that parking can be interpreted as a state of stopping or not moving for a while and being abandoned by the driver. The existence of a parking lot is very helpful for the community, especially for those who have vehicles, you can imagine if there is no parking space. In the concept of this scientific paper using the normative juridical research method. As well as using data collection techniques carried out using descriptive analysis techniques, with secondary data sources, which include primary legal materials such as laws and regulations relating to the Regional Regulation of Indramayu Regency Number 16 of 2017 concerning Parking Management. The purpose of this study is to find out where special parking spaces can be established in the Cimanuk Indramayu culinary tourism object based on Regional Regulation Number 16 of 2017 concerning Parking Implementation and to find out the management of parking special areas in Indramayu based on Regional Regulation of Indramayu Regency Number 16 of 2017 concerning Parking Implementation. The results of this study indicate that in the implementation of Parking Management in Indramayu Regency, it has been regulated in the Regional Regulation of Indramayu Regency Number 16 of 2017 concerning Parking Management and has been in accordance with applicable regulations. But in its implementation, this is not like that because in implementation, the parking lot is a utility, only useful for local governments for regional income but for the community it is very burdensome.